Return of the Thin Man [compact disc, unabridged] - Hammett, Dashiell, 1894-1961 (HighBridge Audio, 2012)
Following the enormous success of 'The Thin Man' movie in 1934, Hammett was commissioned to write stories for additional films. He wrote two full-length novellas for the films that became 'After the Thin Man' and 'Another Thin Man,' in which he brought back his classic characters, retired private investigator Nick Charles and his former debutante wife Nora, written with classic, barbed Hammett dialogue.